Designing large-sized cocatalysts for fast charge separation towards highly efficient visible-light-driven hydrogen evolution. (13th August 2021) - Zhang, Hang; Li, Yuanli; Li, Weiming; Zhuang, Chunqiang; Gao, Chunlang; Jiang, Wenshuai; Sun, Wei; Qi, Kezhen; Sun, Zaicheng; Han, Xiaodong
Abstract: A key challenge in photocatalysts is their rapid recombination of photo-generated electron-hole pairs. To decrease the recombination probability, significant studies have been devoted to increasing potential active sites of photocatalytic systems for fast charge separation. Here we demonstrate a strategy to boost active sites that is different from conventional approaches, in which large-sized Mxene nanosheets were employed as cocatalysts, while small-sized CdS nanosheets were used as photocatalysts forming effective nanocomposites. Based on our designed strategy, the enrichment of transfer routes guides the fast separation of electrons from CdS nanosheets and transferred onto large-sized Mxene nanosheets. The visible-light-driven hydrogen production of our innovatively designed composites has been improved from 2.8 mmol/g of pure CdS nanosheets to 17.5 mmol/g of the CdS@Mxene optimized composite. The obvious improvement of hydrogen production verifies the feasibility of our design strategy as a unique way to design photocatalytic systems for fast charge separation and highly efficient photocatalytic properties. Highlights: A game-changing design of photocatalytic system. Engineering Low-cost, large-size, and ultra-thin cocatalyst. Design of ultra-thin and small-sized photocatalyst. Anchoring small-sized photocatalyst onto large-sized cocatalyst. Highly improved hydrogen evolution based on the new designed photocatalytic system.